Promoting Engagement in the English Language Learning Through the Use of Visual Aids (2017)
ABSTRACT: This action research project was developed in order to comprehend how the use of visual learning aids would be able to promote, for the students, the engagement in the English language learning process, as a foreign language. This action research was put into action at Institución Educativa Juan María Céspedes, throughout two school periods, for second grade students. The methods used to collect the data from the students; cooperating teacher and school were the observations, an interview and a survey, which were taken for triangulation as a way of analyzing what was explored and evinced. Findings disclosed that activities conducted by means of visual learning aids not just promoted the students’ engagement in learning English, but they might also bring some benefits such as students’ attention improvement, facilitating students’ understanding of the topics, words and expressions, and raising students’ participation in class. Key words: Engagement, visual learning aids, students' understanding.